Beyond the grid: Navigating water supply and sanitation service ecosystems in informal settlements - Ana Casas; Paul Hutchings; Andrew R. Bell; Beata Kupiec-Teahan; Amy R. Lewis; José Mendoza Sanchez; Simon Willcock; Fiona Anciano; Dani J. Barrington; Mmeli Dube; Caroline Karani; Arturo Llaxacondor; et al. (PLoS ONE, 2026)
Hundreds of millions of people living in urban informal settlements rely on irregular and unsafe water supply and sanitation services. To meet their needs, they must navigate fragmented service delivery environments and use multiple different water and sanitation facilities. Using high-frequency longitudinal survey data from three informal settlements in Kenya, Peru and South Africa, we document the variability in water supply and sanitation service access. Across the year-long study period, 62–73% of respondents across all contexts changed their primary toilet, with 10–27% reporting five or more different primary facilities, with similar variability in water access. High levels of disruption were reported, with issues related to crowding/queuing, breakdowns, and physical barriers disrupting accessibility all contributing to the churn of services. To explain the results, we develop the concept of a “service ecosystem” to describe how people living in urban informal settlements rely on multiple water supply and sanitation services simultaneously and how these patterns of access shift over time. Using James C Scott’s theory of legibility, we argue that this irregularity means these service ecosystems are largely illegible within formal monitoring frameworks, that typically categorise households by a primary service. This leads to an information deficit for policymakers and practitioners who have a mandate to improve services in these environments. We further develop the implications of service ecosystems by calling for policymakers and service providers to recognise and support a diversity of service systems which have sufficient redundancy between them to meet the needs of populations, at least until broader structural reforms can address the underlying challenges in these settings.